Induction of Proteinuria by Cannabinoid Receptors 1 Signaling Activation in CB1 Transgenic Mice. (February 2015) - Hsu, Yung-Chien; Lei, Chen-Chou; Shih, Ya-Hsueh; Ho, Cheng; Lin, Chun-Liang
Abstract : Abstract: Proteinuria is not only a sign of kidney damage but is also involved in the progression of renal disease as an independent pathologic factor. Although patients with mutated type 1 cannabinoid receptors (C B 1) polymorphism are associated with renal microvascular damage, the biologic role of C B 1 signaling in proteinuria remains uncharacterized till now. Herein, we investigate whether C B 1 participates in glomerular proteinuria in C B 1 transgenic mice and treatment with C B 1 agonist WIN55212-2 rat, neither of which are diabetic models. The C B 1 transgenic mice and rats treated with C B 1 agonist WIN55212-2 had higher kidney weight and urinary protein concentrations but not blood glucose levels compared with the wild-type group. A combination of laser-capture microsdissection, quantitative reverse transcription–polymerase chain reaction, immunoblotting and immunohistochemical validation revealed that C B 1 transgenic mice and rats treated with C B 1 agonist WIN55212-2 had higher vascular endothelial growth factor (VEGF) expression in renal glomeruli than that of the wild-type group. Geneticorpharmacological activation of C B 1 by transgenic C B 1 mice or treatment with WIN55212-2 reduced nephrin expression in the renal glomeruli compared with that of the wild-type group in the glomerular mesanglium. Taken together, C B 1 transgenic mice and rats treated with C B 1 agonist WIN55212-2 induced proteinuria with upregulation of C B 1 resulting in impaired nephrin expression, by inducing excess VEGF reaction in the renal glomeruli. Genetic and pharmacological manipulation of C B 1 signaling revealed VEGF-dependent nephrin depression of glomerulopathy. Controlling C B 1 activity can be used an alternative strategy for sustaining renal function in the presence of C B 1 activation.